Dealing with existing theory: national fatality rates, vehicle standards and personal safety. Issue 1 (2nd January 2020) - Mohan, Dinesh; O'Neil, Brian
Abstract: In this paper we discuss some of the weaknesses in exiting theories and understandings behind road safety interventions and policy making. The paper deals with four main issues: road traffic fatality rates and per capita income of countries, vehicle crashworthiness standards, role of pedestrian and powered two-wheeler share in traffic on fatalities, and safety standards for vehicles other than cars. Recent data indicate that there may not be a strong relationship between income and road safety performance and it is possible for low and middle-income countries (LMIC) to decrease death rates at present income levels. Safer cars have had a major role in reducing fatality rates, but, gains in traffic safety in high income countries may be partly due to reducing exposure of vulnerable road users. Small lightweight vehicles (like tuk-tuks, three-wheeled scooter taxis) operating in many LMIC appear to have low fatality rates though they do not follow any crashworthiness standards. Very different crashworthiness standards need to be developed for low mass vehicles incapable of operating speeds greater than 50 km/h. LMIC may not be able to reduce fatality rates below about 7 per 100, 000 population unless there are innovative developments in road design and all vehicle safety standards.